Laparoscopic Versus Open Liver Resection for Tumors in the Posterosuperior Segments: A Systematic Review and Meta-analysis. Issue 2 (April 2020) - Hajibandeh, Shahab; Hajibandeh, Shahin; Dave, Madhav; Tarazi, Munir; Satyadas, Thomas
Abstract : Objective: The objective of this study was to compare the outcomes of laparoscopic and open liver resection for tumors in the posterosuperior segments. Methods: We performed a systematic review in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement standards. We conducted a search of electronic information sources to identify all studies comparing outcomes of laparoscopic and open liver resection for tumors in the posterosuperior segments. We used the Risk Of Bias In Nonrandomized Studies—of Interventions (ROBINS-I) tool to assess the risk of bias of the included studies. Fixed-effect or random-effects models were applied to calculate pooled outcome data. Results: We identified 11 observational studies, enrolling a total of 1023 patients. The included population in both groups were comparable in terms of baseline characteristics. Laparoscopic approach was associated with lower risks of total complications [odds ratio (OR): 0.45; 95% confidence interval (CI): 0.33, 0.61; P <0.00001], major complications (Dindo-Clavien III or more) (OR: 0.52; 95% CI: 0.36, 0.73; P =0.0002), and intraoperative blood loss [mean difference (MD): −114.71; 95% CI: −165.64, −63.79; P <0.0001]. Laparoscopic approach was associated with longer operative time (MD: 50.28; 95% CI: 22.29, 78.27; P =0.0004) and shorter length of hospital stay (MD: −2.01; 95% CI: −2.09, −1.92; P <0.00001) compared with open approach. There was no difference between the 2 groups in terms of need for blood transfusion (OR: 1.23; 95% CI: 0.75, 2.02; P =0.41), R0 resection (OR: 1.09; 95% CI: 0.66, 1.81; P =0.72), postoperative mortality (risk difference: −0.00; 95% CI: −0.02, 0.02; P =0.68), and need for readmission (OR: 0.70; 95% CI: 0.19, 2.60; P =0.60). In terms of oncological outcomes, there was no difference between the groups in terms disease recurrence (OR: 1.58; 95% CI: 0.95, 2.63; P =0.08), overall survival (OS) at maximum follow-up (OR: 1.09; 95% CI: 0.66, 1.81; P =0.73), 1-year OS (OR: 1.53; 95% CI: 0.48, 4.92; P =0.47), 3-year OS (OR: 1.26; 95% CI: 0.67, 2.37; P =0.48), 5-year OS (OR: 0.91; 95% CI: 0.41, 1.99; P =0.80), disease-free survival (DFS) at maximum follow-up (OR: 0.91; 95% CI: 0.65, 1.27; P =0.56), 1-year DFS (OR: 1.04; 95% CI: 0.60, 1.81; P =0.88), 3-year DFS (OR: 1.13; 95% CI: 0.75, 1.69; P =0.57), and 5-year DFS (OR: 0.73; 95% CI: 0.44, 1.24; P =0.25). Conclusions: Compared with the open approach in liver resection for tumors in the posterosuperior segments, the laparoscopic approach seems to be associated with a lower risk of postoperative morbidity, less intraoperative blood loss, and shorter length of hospital stay with comparable survival and oncological outcomes. The best available evidence is derived from observational studies with moderate quality; therefore, high-quality randomized controlled trials with adequate statistical power are required to provide a more robust basis for definite conclusions. Abstract : Supplemental Digital Content is available in the text.